Preparation method of ceramic membrane with efficient separation and catalysis functions as well as product and application of ceramic membrane

By adopting the combination of large -scale ceramic particles and small -particle -size ceramic particles, the ceramic membrane with sandwiches is prepared, and the restrictions between the signs of the separation efficiency and catalytic function of the traditional catalytic ceramic film are solved, and the efficient separation and catalysis have been achieved. Degraded function.

CN119327285AActive Publication Date: 2025-01-21JINGDEZHEN CERAMIC UNIV

Patent Information

Application Number
CN202411775138.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-21
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

When traditional catalytic ceramic membranes treat wastewater, catalytic active sites are easily covered by membrane contamination, resulting in a trade-off between separation efficiency and catalytic function, and cannot have both efficient separation and catalytic degradation functions.

Method used

The high -particle -size ceramic particles are used to prepare the high -throughput ceramic film support body. The transition layer is prepared by the grining legal system, and a small -particle -size ceramic particles are used to prepare a separate film layer with immersion method.

Benefits of technology

It increases the number of catalytic active sites and the generation efficiency of ROS, enhances the separation efficiency of particulate matter and organic matter in water, avoids membrane fouling, and achieves simultaneous improvement of ceramic membrane separation efficiency and catalytic degradation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327285A_ABST
    Figure CN119327285A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a ceramic membrane with efficient separation and catalysis functions as well as a product prepared by the preparation method and application of the ceramic membrane. The preparation method comprises the following steps: preparing a ceramic membrane support body by taking large-particle-size ceramic particles as a raw material, and preparing a transition layer by taking transition metal oxide nanofibers as a raw material by adopting a dip coating method; small-particle-size ceramic particles are used as raw materials to prepare a separation membrane layer by adopting a dip-coating method, and the ceramic membrane with a sandwich structure is formed through one-step co-firing. The transition layer with high porosity and specific surface area is formed by adopting the transition metal oxide nanofibers, so that the number of catalytic active sites and the permeation flux are improved; small-particle-size ceramic particles are adopted to form a separation membrane layer with uniform pore size distribution and a flat membrane surface, so that the separation efficiency of particulate matters and organic matters in water is improved, the accumulation of the particulate matters and the organic matters on the membrane surface is reduced, and meanwhile, the particulate matters and the organic matters in water are prevented from covering active sites of the catalytic ceramic membrane; therefore, the separation efficiency and the catalytic degradation efficiency of the ceramic membrane are synchronously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membrane separation technology, and in particular to a method for preparing a ceramic membrane having both efficient separation and catalytic functions, and a product and application thereof. Background Art

[0002] New pollutants exist in all kinds of sewage and wastewater, which seriously threaten the ecological environment and human health. Catalytic ceramic membranes coupled with advanced oxidation processes are considered to be a feasible technology for removing new pollutants from sewage and wastewater. However, the preparation of traditional catalytic ceramic membranes is to load transition metal nanopowders inside the membrane pores of the ceramic membrane. For example, the catalytic ceramic membrane is prepared by the metal precursor impregnation method. Since the particle size of the transition metal nanopowders after calcination is relatively large, the specific surface area and catalytic active sites of the catalytic ceramic membrane are relatively small, the reaction efficiency of the active oxygen components (ROS) and the new pollutant molecules is limited, and the new pollutant removal efficiency is low.

[0003] To this end, the existing technology uses nanofiber catalysts and single-atom catalysts with high specific surface areas as membrane layers, thereby increasing the number of active sites of the catalytic ceramic membrane and the efficiency of ROS generation, and promoting the efficient removal of new pollutants. However, sewage and wastewater often contain various organic matter and small particles, which inevitably cause membrane pollution during membrane operation, resulting in failure of catalytic active sites and reducing the contact efficiency between catalytic active sites and oxidants, which seriously limits the efficient removal of new pollutants in sewage and wastewater.

[0004] Especially for the situation where particulate matter, macromolecular organic matter and new pollutants coexist in sewage and wastewater, since new pollutants are more soluble organic matter, while particulate matter and macromolecular organic matter are insoluble. In this way, even if the catalytic ceramic membrane prepared based on nanofiber catalysts and single-atom catalysts can efficiently catalytically remove new pollutants in water and alleviate membrane pollution, the membrane surface of the nanofiber catalytic ceramic membrane is non-planar and the pore size distribution is uneven, resulting in low separation efficiency and serious membrane pollution, and it is impossible to have both efficient separation and catalytic degradation functions. Although the single-atom catalytic ceramic membrane has a flat membrane surface and high catalytic efficiency, it can achieve efficient removal of new pollutants and efficient separation of particulate matter and macromolecular organic matter in water, but it still cannot avoid the accumulation of particulate matter and macromolecular organic matter in water on the membrane surface, thereby covering some catalytic active sites, reducing the utilization efficiency of catalytic active sites, and inhibiting the generation efficiency of ROS, resulting in a trade-off between the separation efficiency and catalytic function of the catalytic ceramic membrane. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a ceramic membrane with both efficient separation and catalytic functions, wherein a high-flux ceramic membrane support is prepared using large-size ceramic particles as raw materials, and a transition layer is prepared using transition metal oxide nanofibers as raw materials by a slurry dipping method. On this basis, a separation membrane layer is prepared using small-size ceramic particles as raw materials by a dip coating method, and the transition layer and the separation membrane layer are co-fired in one step to form a ceramic membrane with a sandwich structure and both efficient separation and catalytic functions. Another purpose of the present invention is to provide products and applications obtained by using the above-mentioned method for preparing a ceramic membrane with both efficient separation and catalytic functions.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a ceramic membrane having both efficient separation and catalytic functions, comprising the following steps:

[0008] (1) Preparation of ceramic membrane support

[0009] After mixing coarse ceramic particles with an average particle size of 5 to 80 μm with a pore former and a binder, a ceramic membrane support is prepared by dry pressing, and calcined at 1300 to 1650° C. for 2 to 4 hours to obtain a ceramic membrane support with an average pore size of 1 to 6 μm; the amounts of the pore former and the binder are 5 to 15 wt% and 0.5 to 1.2 wt% of the coarse ceramic particles, respectively;

[0010] (2) Preparation of transition layer by slurry dipping method

[0011] (2-1) adding transition metal oxide nanofibers having a diameter of 20 to 100 nm and an aspect ratio of 20 to 50, a dispersant and a stabilizer to water, and stirring to obtain a transition layer slurry having a solid content of 10 to 20%; the amounts of the dispersant and the stabilizer are 0.2 to 0.8 wt % and 1.2 to 2.5 wt % of the transition metal oxide nanofibers, respectively;

[0012] (2-2) immersing the ceramic membrane support in a transition layer slurry for 10 to 30 seconds, 1 to 5 times, with a membrane thickness of 60 to 150 μm, and then taking out and drying to obtain a ceramic membrane with a transition layer;

[0013] (3) Preparation of separation membrane layer by dip coating

[0014] (3-1) adding fine ceramic particles with an average particle size of ≤500 nm, a dispersant and a stabilizer into water, stirring and ultrasonically dispersing to obtain a separation membrane slurry with a solid content of 15-25%; the amount of the pore former and the stabilizer is 0.5-1.5wt% and 1.5-3.5wt% of the fine ceramic particles, respectively;

[0015] (3-2) immersing a ceramic membrane having a transition layer in a separation membrane layer slurry, taking it out and drying it, thereby obtaining a ceramic membrane having a transition layer and a separation membrane layer;

[0016] (4) Preparation of ceramic membrane

[0017] The ceramic membrane with the transition layer and the separation membrane layer is calcined at a temperature of 900-1300°C and a holding time of 1-2h to obtain a ceramic membrane with both efficient separation and catalytic functions, with a porosity of more than 45% and a pore size of 10-200nm.

[0018] Furthermore, the ceramic particles of the present invention are one of aluminum oxide, zirconium oxide, silicon carbide, cordierite or a combination thereof. The transition metal oxide nanofibers are one of manganese oxide fibers, titanium dioxide fibers, iron oxide fibers or a combination thereof.

[0019] In the above scheme, the dispersant of the present invention is one or more of Dolapix series dispersants, sodium hexametaphosphate, and polyethyleneimine, wherein polyethyleneimine is not compatible with Dolapix series dispersants; the stabilizer is one or a combination of sodium carboxymethyl cellulose, methyl cellulose, and polyvinyl alcohol.

[0020] The product is made by using the above-mentioned method for preparing the ceramic membrane with both high-efficiency separation and catalytic functions.

[0021] The application of the product of the present invention is as follows: the ceramic membrane product is coupled / activated oxidant continuous flow process is used to degrade new pollutants in water. When the concentration of new pollutants is 1-20 mg / L, the TOC of the influent is 5-25 mg / L, and the COD Mn 20~200mg / L, turbidity 0.5~3.0NTU, UV 254 0.1~1.8cm -1 According to the molar ratio of oxidant: new pollutant = 1: 0.03-0.1, when the membrane flux is 100-150LMH, the degradation efficiency of new pollutants in the catalytic reaction process of continuous 1-24h is 100%, and the TOC of membrane effluent is 0-1.5mg / L, COD Mn 0~20mg / L, turbidity 0~1.0, UV 254 0~0.8cm -1 .

[0022] In the above scheme, the oxidants used in the present invention are persulfate, hydrogen peroxide, ozone, and peracetic acid; the new pollutants are bisphenol A, ibuprofen, sulfamethoxazole, tetracycline, amoxicillin and other medicines and care products, and endocrine disruptors.

[0023] The present invention has the following beneficial effects:

[0024] (1) The present invention uses transition metal oxide nanofibers as a transition layer and small-size ceramic particles as a separation membrane layer. The transition membrane layer formed by the transition metal oxide nanofibers has a high porosity and specific surface area, which increases the number of catalytic active sites, the generation rate of ROS and the permeation flux; the separation membrane layer formed by the small-size ceramic particles has a uniform pore size distribution and a flat membrane surface, which improves the separation efficiency of particulate matter and organic matter in water, reduces their accumulation on the membrane surface, and alleviates membrane pollution. At the same time, it avoids the coverage of the active sites of the catalytic ceramic membrane by particulate matter and organic matter in the water, thereby achieving a simultaneous improvement in the separation efficiency of the ceramic membrane and the catalytic degradation efficiency.

[0025] (2) The transition metal oxide nanofibers of the present invention are used as the raw material of the transition layer, and they are randomly stacked to form a three-dimensional grid structure, which effectively prevents the transition layer slurry from leaking into the interior of the support body. The thickness of the transition layer is adjusted by controlling the number of dip coatings, thereby achieving controllable preparation of the membrane layer. At the same time, an entangled structure is formed between the transition metal oxide nanofibers, which prevents the generation of cracks in the membrane layer, providing a guarantee for the preparation of high-performance separation membrane layers.

[0026] (3) The present invention utilizes a slurry impregnation method to prepare a transition layer and a separation membrane layer, and adopts a co-firing process of the transition layer and the separation membrane layer to prepare a ceramic membrane, thereby simplifying the preparation process and reducing the preparation cost of the catalytic ceramic membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings:

[0028] Figure 1 The following are scanning electron microscope photographs of the surface and cross-section of the ceramic membrane prepared in Example 1 of the present invention (a: surface; b: cross-section). DETAILED DESCRIPTION

[0029] Embodiment 1:

[0030] 1. This embodiment provides a method for preparing a ceramic membrane having both efficient separation and catalytic functions, and the steps are as follows:

[0031] (1) Preparation of ceramic membrane support

[0032] 100 g of alumina coarse particles with an average particle size of 20 μm were mixed with 10 g of corn starch and 0.8 g of sodium carboxymethyl cellulose, and a ceramic membrane support was prepared by dry pressing (pressure of 12 MPa), and calcined at 1450° C. for 3 h to obtain a ceramic membrane support with an average pore size of 2.5 μm;

[0033] (2) Preparation of transition layer by slurry dipping method

[0034] (2-1) 10 g of titanium dioxide nanofibers with a diameter of 30 nm and a length of 800 nm, 0.05 g of sodium hexametaphosphate, and 0.13 g of polyvinyl alcohol were added to 100 g of pure water, and magnetic stirring was performed for 30 min (300 r / min) to obtain a transition layer slurry;

[0035] (2-2) immersing the ceramic membrane support body in the transition layer slurry for 25 seconds and once, taking it out and placing it in a constant temperature and humidity drying oven (temperature: 90° C., humidity: 60%) for drying to obtain a ceramic membrane with a transition layer;

[0036] (3) Preparation of separation membrane layer by dip coating

[0037] (3-1) 15 g of alumina fine particles with an average particle size of 100 nm, 0.08 g of polyethyleneimine, and 0.18 g of polyvinyl alcohol were added to 100 g of pure water, magnetically stirred for 20 min (350 r / min), and ultrasonically dispersed for 5 min to obtain a separation membrane slurry;

[0038] (3-2) immersing the ceramic membrane with the transition layer in the separation membrane layer slurry for 20 seconds and once, taking it out and placing it in a constant temperature and humidity drying oven (temperature: 80° C., humidity: 50%) for drying to obtain a ceramic membrane with a transition layer and a separation membrane layer;

[0039] (4) Preparation of ceramic membrane

[0040] The ceramic membrane with the transition layer and the separation membrane layer is placed in an electric furnace for calcination at a temperature of 1100°C and a holding time of 2 hours to obtain a ceramic membrane with both high efficiency separation and catalytic functions (see Figure 1 ). The porosity of the ceramic membrane is 50% and the average pore size is 30 nm.

[0041] 2. The ceramic membrane activated persulfate continuous flow process prepared in this example degrades ibuprofen in ultrapure water, with an influent TOC of 5.5 mg / L and a COD Mn is 25.5mg / L, turbidity is 0.72NTU, UV 254 0.21cm -1 When the peroxymonosulfate concentration was 0.8 mM, the ibuprofen concentration was 10 mg / L, and the membrane flux was 100 LMH, the degradation efficiency of ibuprofen was 100% in the 12 h continuous catalytic reaction, and the TOC of the membrane effluent was 0.5 mg / L, COD Mn is 5.8mg / L, turbidity is 0.51NTU, UV 254 0.13cm -1 .

[0042] Embodiment 2:

[0043] This embodiment provides a method for preparing a ceramic membrane having both efficient separation and catalytic functions, and the steps are as follows:

[0044] (1) Preparation of ceramic membrane support

[0045] 100 g of alumina coarse particles with an average particle size of 40 μm were mixed with 10 g of corn starch and 0.8 g of sodium carboxymethyl cellulose, and a ceramic membrane support was prepared by dry pressing (pressure of 12 MPa), and calcined at 1550° C. for 2 h to obtain a ceramic membrane support with an average pore size of 3.2 μm;

[0046] (2) Preparation of transition layer by slurry dipping method

[0047] (2-1) 10 g of manganese oxide nanofibers with a diameter of 40 nm and a length of 900 nm, 0.05 g of sodium hexametaphosphate, and 0.13 g of polyvinyl alcohol were added to 100 g of pure water, and magnetic stirring was performed for 30 min (300 r / min) to obtain a transition layer slurry;

[0048] (2-2) immersing the ceramic membrane support body in the transition layer slurry for 25 seconds and once, taking it out and placing it in a constant temperature and humidity drying oven (temperature: 90° C., humidity: 60%) for drying to obtain a ceramic membrane with a transition layer;

[0049] (3) Preparation of separation membrane layer by dip coating

[0050] (3-1) 15 g of alumina fine particles with an average particle size of 200 nm, 0.08 g of polyethyleneimine, and 0.18 g of polyvinyl alcohol were added to 100 g of pure water, and magnetic stirring was performed for 20 min (350 r / min), and ultrasonic dispersion was performed for 5 min to obtain a separation membrane slurry;

[0051] (3-2) immersing the ceramic membrane with the transition layer in the separation membrane layer slurry for 20 seconds and once, taking it out and placing it in a constant temperature and humidity drying oven (temperature: 80° C., humidity: 50%) for drying to obtain a ceramic membrane with a transition layer and a separation membrane layer;

[0052] (4) Preparation of ceramic membrane

[0053] The ceramic membrane with the transition layer and the separation membrane layer is placed in an electric furnace for calcination at a temperature of 1200°C and a holding time of 2 hours to obtain a ceramic membrane with both efficient separation and catalytic functions. The porosity of the ceramic membrane is 55% and the average pore size is 50nm.

[0054] 2. The ceramic membrane activated persulfate continuous flow process prepared in this example degrades bisphenol A in surface water, with an influent TOC of 15 mg / L and a COD Mnis 120mg / L, turbidity is 2.1NTU, UV 254 1.2cm -1 When the peroxymonosulfate concentration was 1.0 mM, the ibuprofen concentration was 15 mg / L, and the membrane flux was 120 LMH, the degradation efficiency of bisphenol A in the catalytic reaction for 12 hours was 100%, and the TOC in the membrane effluent was 1.5 mg / L, COD Mn is 20mg / L, turbidity is 0.5NTU, UV 254 0.21cm -1 .

Claims

1. A method for preparing a ceramic membrane with both efficient separation and catalytic functions, characterized in that The following steps are involved: (1) Preparation of ceramic membrane support After mixing coarse ceramic particles with an average particle size of 5 to 80 μm with a pore former and a binder, a ceramic membrane support is prepared by dry pressing, and calcined at 1300 to 1650° C. for 2 to 4 hours to obtain a ceramic membrane support with an average pore size of 1 to 6 μm; the amounts of the pore former and the binder are 5 to 15 wt% and 0.5 to 1.2 wt% of the coarse ceramic particles, respectively; (2) Preparation of transition layer by slurry dipping method (2-1) adding transition metal oxide nanofibers having a diameter of 20 to 100 nm and an aspect ratio of 20 to 50, a dispersant and a stabilizer to water, and stirring to obtain a transition layer slurry having a solid content of 10 to 20%; the amounts of the dispersant and the stabilizer are 0.2 to 0.8 wt % and 1.2 to 2.5 wt % of the transition metal oxide nanofibers, respectively; (2-2) immersing the ceramic membrane support in a transition layer slurry for 10 to 30 seconds, 1 to 5 times, with a membrane thickness of 60 to 150 μm, and then taking out and drying to obtain a ceramic membrane with a transition layer; (3) Preparation of separation membrane layer by dip coating (3-1) adding fine ceramic particles with an average particle size of ≤500 nm, a dispersant and a stabilizer into water, stirring and ultrasonically dispersing to obtain a separation membrane slurry with a solid content of 15-25%; the amount of the pore former and the stabilizer is 0.5-1.5wt% and 1.5-3.5wt% of the fine ceramic particles, respectively; (3-2) immersing a ceramic membrane having a transition layer in a separation membrane layer slurry, taking it out and drying it, thereby obtaining a ceramic membrane having a transition layer and a separation membrane layer; (4) Preparation of ceramic membrane The ceramic membrane with the transition layer and the separation membrane layer is calcined at a temperature of 900-1300°C and a holding time of 1-2h to obtain a ceramic membrane with both efficient separation and catalytic functions, with a porosity of more than 45% and a pore size of 10-200nm.

2. The method for preparing a ceramic membrane having both efficient separation and catalytic functions according to claim 1, characterized in that: The ceramic particles are one of aluminum oxide, zirconium oxide, silicon carbide and cordierite or a combination thereof.

3. The method for preparing a ceramic membrane having both efficient separation and catalytic functions according to claim 1, characterized in that: The transition metal oxide nanofibers are one of manganese oxide fibers, titanium dioxide fibers, and iron oxide fibers, or a combination thereof.

4. The method for preparing a ceramic membrane having both efficient separation and catalytic functions according to claim 1, characterized in that: The dispersant is one or more of Dolapix series dispersants, sodium hexametaphosphate, and polyethyleneimine, wherein polyethyleneimine is not compatible with Dolapix series dispersants; the stabilizer is one or a combination of sodium carboxymethyl cellulose, methyl cellulose, and polyvinyl alcohol.

5. A product obtained by the method for preparing a ceramic membrane having both efficient separation and catalytic functions as described in any one of claims 1 to 4.

6. Use of the product according to claim 5, characterized in that: The ceramic membrane product is coupled / activated oxidant continuous flow process to degrade new pollutants in water. When the concentration of new pollutants is 1-20 mg / L, the TOC of influent is 5-25 mg / L, and the COD Mn 20~200mg / L, turbidity 0.5~3.0NTU, UV 254 0.1~1.8cm -1 According to the molar ratio of oxidant: new pollutant = 1: 0.03-0.1, when the membrane flux is 100-150LMH, the degradation efficiency of new pollutants in the catalytic reaction process of continuous 1-24h is 100%, and the TOC of membrane effluent is 0-1.5mg / L, COD Mn 0~20mg / L, turbidity 0~1.0, UV 254 0~0.8cm -1 .

7. The use according to claim 6, characterized in that: The oxidants are persulfate, hydrogen peroxide, ozone, and peracetic acid; the new pollutants are bisphenol A, ibuprofen, sulfamethoxazole, tetracycline, amoxicillin drugs and care products, and endocrine disruptors.

Citation Information

Patent Citations

  • Assembly of catalytic separation membrane with adjustable interface catalytic performance, and application method of catalytic separation membrane in water treatment

    CN110436607A

  • Ceramic ultrafiltration membrane with catalytic function and preparation method and application thereof

    CN113713627A

  • Electronic apparatus including cooling fan and method for controlling the same

    KR1020230057825A

  • Filtration membrane and methods of use and manufacture thereof

    US20200353424A1

Cited By

  • Carbonized Co-MOF powder, supported membrane, sandwich structure confinement catalytic membrane and preparation method

    CN119926404A

  • Carbonized Co-MOF powder, supported film, sandwich-structured confined catalytic film and preparation method

    CN119926404B

  • Dynamic catalytic ceramic membrane filtering device for efficient treatment of complex wastewater

    CN121591329A

  • Preparation method of metal-based ceramic composite membrane with ozone catalysis function

    CN121623584A

  • Composite membrane with functions of adsorption separation and catalytic degradation of new pollutants as well as preparation method and application of composite membrane

    CN121911246A